The Effectiveness of Pre- and Postoperative Infliximab in Controlling Behçet’s Disease Posterior Uveitis in Patients Undergoing Vitrectomy: A Preliminary Study - Hossam El Din Mohamed Khalil; Heba A. El Gendy; Hala Ahmed Raafat; Hazem Effat Haroun; Tamer Atef Gheita; Hossam Mahmoud Bakir (Journal of Ophthalmology)
Purpose. To evaluate the short-term effectiveness of infliximab in controlling ocular manifestations in Behçet’s Disease (BD) patients candidate for pars plana vitrectomy, if given in a regimen before and after the planned procedure. Patients and Methods. 30 eyes of 27 adult male BD patients with a mean age of 35.56 yrs presented with refractory posterior uveitis not responding to immunosuppressive drugs and candidate for vitrectomy were included. Infliximab was given in a dose of 5 mg/kg intravenous infusion once every two weeks for 3 treatment sessions before the intended vitrectomy followed by 3 treatment sessions at two-week intervals, after vitrectomy. Results. Improvement of ocular manifestations was noted in all eyes, with complete resolution in 26 eyes (87%). Visual acuity improved from 0.23 ± 0.11 to 0.38 ± 0.17 (p≤0.2), ESR decreased from 65.92 mm/hr ± 17.32 SD to 24.93 mm/hr ± 5.28 SD at the last treatment cycle (p≤0.1). The mean daily dose of systemic corticosteroids was tapered from 44.54 mg/d ± 2.89 to 8.48 mg/d ± 6.38 (p≤0.2), and no relapses were noted during the follow-up period. Conclusion. Infliximab may be safe and effective in controlling posterior uveitis and inducing remissions if given in a regimen before and after vitrecomy in BD patients.